Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Coffee Shop Rimbun Di Kota Padang - Alfito Firnando Yunus; Nofri Yendra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research is a survey study of customers at the Rimbun Expresso & Brew coffee shop in Padang City. The title of this research is "The Influence of Product Quality, Price, and Service Quality on Purchase Decisions at the Rimbun Expresso & Brew Bar Coffee Shop in Padang City." The purpose of this research is to determine the influence of Product Quality, Price, and Service Quality on Purchase Decisions at the Rimbun Expresso & Brew Bar Coffee Shop in Padang City. This type of research is quantitative research, and the data collection method uses questionnaires. The population in this study consists of people who have made purchases from the coffee shop Rimbun Expresso & Brew Bar, the number of whom is unknown. The sample size taken in this study is 100 respondents. The sampling technique suggests that the minimum sample size is 5 times the number of statement items in the research questionnaire. In this study, the total number of items is 20 indicators, consisting of 14 indicators for the independent variable and 6 indicators for the dependent variable. Therefore, the sample size for this study is 20 x 5 = 100. Based on the research results and data analysis using SPSS software, it shows that: (1) product quality has a positive and significant effect on purchasing decisions at Rimbun Expresso & Bar Coffee Shop in Padang City, (2) price has a positive and significant effect on purchasing decisions at Rimbun Expresso & Bar Coffee Shop in Padang City, (3) service quality has a positive and significant effect on purchasing decisions at Rimbun Expresso & Bar Coffee Shop in Padang City, (4) product quality, price, and service quality have a positive and significant effect on purchasing decisions at Rimbun Expresso & Bar Padang.